Bintan Image Formation via Instagram in The Pre- And Post-Covid-19 Pandemic Period: A Comparative Study Between Projected Image and Perceived Image - Taufiqqurrachman, Taufiqqurrachman; Poti, Jamhur; Sophia, Uly; Afnira, Ella (Relevance: Journal of Management and Business, 2024)
Several studies have proven that visual content uploaded on Instagram is a factor in forming destination images. On the other hand, tourists and local tourism authorities are two elements that form a destination image. This research aims to identify the image formation projected by local authorities and the image perceived by tourists through visual content uploaded to their official Instagram accounts in two time periods (before and after the COVID-19 pandemic). All visual content uploaded to their Instagram accounts was collected and analyzed using qualitative content analysis techniques to identify differences and similarities in the images formed by these elements in the two highlighted periods. This research found several things. First, various themes are exploited by these two elements in the production of visual content to be uploaded to their Instagram accounts, including natural attractions (AA), cultural attractions (AB), historical and religious buildings (BSK), tourist activities (TA), culinary and restaurant activities (CR), transportation and accommodation (AT), and local people (LP). Second, AA, TA, and AT are the dominant themes in the two periods (pre- and post-COVID-19 pandemic). Third, in the post-pandemic period, there was a significant decline in the population of visual content uploaded to the Genpi-Bintan account compared to the pre-pandemic period. On the other hand, local authority accounts saw an increase in the population of visual content in the post-COVID-19 pandemic period compared to the period before the pandemic. Theoretical and practical implications and several recommendations are presented at the end of this article.